EFEKTIVITAS PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) KERTA SARI UTAMA DI DESA KESIMAN KERTALANGU DAN BUMDES SIMA SARI DANA DI DESA KESIMAN PETILAN DALAM MENINGKATKAN PENDAPATAN ASLI DESA - Windasari, Made Ayu; Winaya, I Ketut; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2019)
ABSTRACT This study was to determiine how effective the Management of Viillage-Owned Enterpriises (BUMDes) iin Kerta Sari Utama in Kesiman Kertalangu Village and BUMDes Sima Sari Dana in Kesiman Petilan Village in Increasing Village Original Revenue (PADes) using effectiveness measures was done through resource approach, process approach, goal approach. This study proves that the management of BUMDes Kerta Sari Utama and BUMDes Sima Sari Dana in improving PADes has been going well but has not been effective because there are still hindrance to the measurement indicators. Keywords: Effectiveness, Village-Owned Enterprises (BUMDes), Village Original Revenue